2022
DOI: 10.1186/s12917-022-03191-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary fibrosis in a dog as a sequela of infection with Severe Acute Respiratory Syndrome Coronavirus 2? A case report

Abstract: Background Interstitial lung disease is a heterogeneous group of conditions characterized by severe radiographic changes and clinicopathological findings. However, in the vast majority of cases, the cause remains unknown. Case description In the present study, we reported the clinical case of a 3 years old female Bull Terrier presented in October 2020 to the Advanced Diagnostic Imaging Department of the Turin Veterinary Teaching Hospital with a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Mild clinical signs have been reported in cats after experimental infection, whereas dogs did not show any clinical signs. Some case reports describe clinical symptoms in dogs and cats with SARS‐CoV‐2, mostly from the respiratory and gastro‐intestinal tract (Miró et al., 2021 ; Colitti et al., 2022 ). In our HH study, about one‐third of owners reported clinical signs in their pets, but this was not associated with the presence of viral RNA and/or antibodies against SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Mild clinical signs have been reported in cats after experimental infection, whereas dogs did not show any clinical signs. Some case reports describe clinical symptoms in dogs and cats with SARS‐CoV‐2, mostly from the respiratory and gastro‐intestinal tract (Miró et al., 2021 ; Colitti et al., 2022 ). In our HH study, about one‐third of owners reported clinical signs in their pets, but this was not associated with the presence of viral RNA and/or antibodies against SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiogenic pulmonary edema (CPE) in the dog is characterized by acute respiratory distress with radiographic evidence of lung infiltrates that resolve with the administration of a diuretic 1,2 . Consideration of etiologies that are associated with transient interstitial to alveolar lung pattern in addition to CPE, include but are not limited to, non‐CPE, pulmonary hypertension, pneumonia, and lung contusion 2‐17 . Distinguishing CPE from other causes of abnormal lung patterns on thoracic radiographs is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…etiologies that are associated with transient interstitial to alveolar lung pattern in addition to CPE, include but are not limited to, non-CPE, pulmonary hypertension, pneumonia, and lung contusion. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Distinguishing CPE from other causes of abnormal lung patterns on thoracic radiographs is challenging. CPE often has accompanying lobar pulmonary vein dilation reflecting venous hypertension but interpretation could be confounded by recent administration of loop diuretics.…”
mentioning
confidence: 99%
“…Indeed, the early human cases of SARS-CoV-2 have been linked back to strict contacts with wildlife in a market in Wuhan [ 20 ]; however, the animal reservoir of this virus is still uncertain, with bats and pangolins suspected to be the most probable candidates [ 21 ]. Neutralizing antibodies in dogs (2.3–3.3%) and cats (5.8–16.2%) living in close contact with SARS-CoV-2-positive humans in geographic areas severely affected by COVID-19 were described in Italian studies [ 10 , 22 ]. Furthermore, cases of mild or severe respiratory disease and asymptomatic infections have also been detected in Italian household cats and dogs [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neutralizing antibodies in dogs (2.3–3.3%) and cats (5.8–16.2%) living in close contact with SARS-CoV-2-positive humans in geographic areas severely affected by COVID-19 were described in Italian studies [ 10 , 22 ]. Furthermore, cases of mild or severe respiratory disease and asymptomatic infections have also been detected in Italian household cats and dogs [ 22 , 23 , 24 ]. However, evidence of infection by SARS-CoV-2 has not always been found in Italian pet animals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%